Mengukur minat berwirausaha dengan menggunakan pendekatan theory of planned behavior dan religiusitas - Maullah, Siti; Rofiuddin, Mohammad (Nur Science Institute, 2021)
The purpose of this study was to examine the effect of behavioral attitudes, subjective norms, perceived behavioral control, and religiosity on interest in entrepreneurship. This type of research is quantitative research. The population used is students of the Faculty of Economics and Islamic Business, Salatiga State Institute of Islamic Religion, with the criteria for students who have taken entrepreneurship courses. The number of samples taken was 271 students with a proportional stratified random sampling technique—data collection method through distributing questionnaires and then analyzed by multiple linear regression. The study results show that, partially, attitude-behavior does not affect an interest in entrepreneurship. At the same time, subjective norms perceived behavioral control and religiosity affect an interest in entrepreneurship. This research can use as a reference for students or further researchers related to entrepreneurial interest seen from the theory of planned behavior and religiosity.